A new species of Aspidiophorus (Gastrotricha: Chaetonotidae) from the Swedish west coast - Kånneby, Tobias; Todaro, M. Antonio (Zootaxa, 2017)
Gastrotricha is a group of small aquatic acoelomate animals with more than 820 species worldwide (Balsamo et al. 2015). The Swedish gastrotrich fauna today comprises 94 nominal species of which 40 are marine and 54 are freshwater (Curini-Galletti et al. 2012; Kånneby 2011). Of these, 69 species belong to the order Chaetonotida Remane, 1925 and 25 species belong to the order Macrodasyida Remane, 1925. Compared to other relatively well investigated countries in the region, the Swedish marine Gastrotrich fauna of the west coast appears fairly surveyed. In fact, 38 species have been recorded from Norway (Clausen 2004; Schmidt 1972), while 15 species have been recorded from the seas surrounding the Danish mainland (Grilli et al. 2010). The Swedish brackish waters of the Baltic have a lower diversity and so far only 7 species are known from this area (Kånneby 2011; unpublished observations). By comparison, 31 species have been recorded from the Polish Baltic coast (Hummon 2008; Kolicka et al. 2015). In this paper we describe a new species of Aspidiophorus found during an intensive research on the gastrotrich fauna of the surroundings of the Sven Lovén Centre for Marine Sciences (Kristineberg) on the Swedish west coast carried out in the summer of 2009.